Konstitusionalitas Penerapan Sanksi Pidana terhadap Kebijakan Publik yang Berimplikasi Pidana - Kholik, Muhamad Abdul; Zulfaidah, Rena; Hakim, Subqi Muhammad Fadhilah (PT. Sharia Journal and Education Center, 2026)
This study examines the constitutionality of imposing criminal sanctions on public policies that have criminal implications. The research is motivated by the increasing phenomenon of policy criminalization, which has created legal uncertainty for public officials in performing governmental duties. The objectives of this study are to analyze the constitutional limits of criminal liability in public policy, to identify the legal problems arising from the criminalization of policy, and to formulate an ideal model for the application of criminal sanctions in accordance with the principles of the rule of law. This research employs a normative legal method with statutory, conceptual, and case approaches. Legal materials were analyzed qualitatively through library research involving legislation, legal doctrines, and relevant court decisions. The findings reveal that not every public policy resulting in loss can be criminalized, but must meet constitutional parameters such as the existence of mens rea, abuse of authority, real and measurable loss, and clear violation of law. The practice of criminalizing public policy generates various problems, including over-criminalization, chilling effects on decision-making, and conflicts between administrative discretion and criminal law enforcement. This study concludes that the application of criminal sanctions to public policy must be positioned as ultimum remedium through the synchronization of administrative law, constitutional law, and criminal law. The proposed ideal model emphasizes the prioritization of administrative sanctions and the formulation of clear legal parameters to ensure that law enforcement remains constitutional, proportional, and supportive of effective governance.